Kritik Sastra Objektif Terhadap Puisi "Perahu Kertas" Karya Sapardi Djoko Damono - Pratiwi, Nadila (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This study aims to analyze the poem Perahu Kertas by Sapardi Djoko Damono through an objective literary criticism approach. The technique used in this study is the reading and note-taking technique. This approach focuses on the study of literary texts as a stand-alone entity, without taking into account the role of the author, reader, or socio-cultural context when the poem was created. Analysis has been carried out on intrinsic elements in the poem such as theme, characters, plot, setting, style, point of view, and morals, to absorb the messages and meanings hidden in the literary work. This study shows that the theme in the poem Perahu Kertas by Sapardi Djoko Damono is childhood hope that develops into a longing for the journey of the meaning of life. The characters in the poem have deep symbolic meanings. The paper boat is a symbol of fragile but meaningful hope in the journey of life, while the figure of the old man symbolizes wisdom in facing the reality of life. The flow of the poem flows chronologically, showing the journey from childhood filled with imagination to deep reflection on the meaning of life in adulthood. The existence of the setting of place, time, and atmosphere provides a strong picture of the symbolic journey, such as the riverbank, ocean, and hill, which depict the stages of life's journey. Sapardi applies a style of language by using symbolic figures of speech, personification, metaphor, and hyperbole, which provide aesthetic depth and strengthen the emotional appeal in his poem. The teachings given illustrate that the hopes achieved in life will go through a winding journey and full of tests, but every event brings valuable wisdom, although it may not always be in line with expectations at the beginning. This study illustrates how intrinsic elements work together to create beautiful and meaningful poetry, and presents deeper insights into how literary works convey messages and reflections on life. It is hoped that the results of this study can provide valuable contributions to the development of literary studies, especially in exploring the poem Perahu Kertas by Sapardi Djoko Damono with an objective approach.